Determination of some physical and mechanical characteristics of date fruit and nut (cv. Mazafati) - Mansoureh, P.; Meisam, M. (International Journal of Agricultural Technology, 2017)
Knowing some physical and mechanical characteristics is an important factor for automating the activities associated with the date. Some physical and mechanical characteristics of date fruit and its nut were evaluated (Mazafati variety). Date samples mean values of width, length, thickness, projected area perpendicular to width, length and thickness were measured as, 22.73mm , 34.60mm, 18.15mm, 710.78mm2, 411.32mm2, 732.21mm2 respectively. Geometric mean diameter, arithmetic mean diameter, sphericity, surface area, porosity, mass, volume, bulk density and true density were also measured as: 24.21mm, 25.16mm, 70%, 1840.80 mm2, 48.67%, 13.10kg, 11.23 cm3, 0.63gr cm-3, 1.17gr cm-3. In mass modeling, results showed that date volume has the highest correlation (0.88) with mass, and then the arithmetic mean diameter has the highest correlation of (0.82). Date thickness correlation index was very low with mass (0.22). The maximum and minimum deformation force for date samples was found perpendicular to length and thickness direction by average values of 11.52N and 8.02N. Deformation force showed decline procedure with its pressure in direction of length, width and thickness. Results also showed that the rotation coefficient of friction was more than static coefficient of friction and static coefficient of friction was more than dynamic coefficient of friction. Highest coefficient of friction was on the rubber surface and lowest on the galvanized steel surface.